PENGARUH IKLAN MEDIA SOSIAL, DESAIN PRODUK, DAN ONLINE CUSTOMER REVIEW SHOPEE TERHADAP MINAT BELI ULANG MASCARA MAYBELLINE DI SOLO RAYA - Alyndria putri carrensia; Budi istiyanto (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research was conducted to determine whether social media advertising, product design, online customer reviews of Shoope influence interest in repurchasing Maybelline Mascara products. The population is consumers of Maybelline Mascara products. The method used for sampling was nonprobability sampling using purposive sampling technique. A sample of 80 respondents who had purchased Maybelline Mascara products in Solo Raya. This research was carried out using quantitative methods by collecting data using a questionnaire in the form of a Google form. Data instrument testing, classical assumption testing, and multiple linear regression analysis with the SPSS program are the techniques used to analyze the data. The results of this research showthat social media advertising does not significantly influence repurchase interest, product design has a significant influence on repurchase interest, online customer review shops do not significantly influence repurchase interest.